The Symbiotic Dance – How Agile Supply Chains and Strategic Marketing Orchestrate Brand Responsiveness to Evolving Consumer Demands - Dzreke, Simon; Dzreke, Semefa Elikplim (Advances in Business & Industrial Marketing Research, 2025)
Purpose: This study aims to develop and validate the Adaptive Brand Ecosystem model, a new framework that integrates marketing intelligence with agile supply chain execution to enhance organizational responsiveness and competitiveness. It hypothesizes that tighter integration between marketing and operations leads to superior market performance and customer retention. Research Design and Methodology: The research employed a quantitative design using cross-sectional data from 214 companies across various global markets. Performance indicators such as response speed, inventory turnover, and customer retention were analyzed to measure the impact of marketing–supply chain integration. Additionally, case studies from Zara and Warby Parker were used to provide qualitative insights into real-world applications of adaptive capabilities. Findings and Discussion: The findings reveal that firms with strong marketing–operations integration respond 68% faster to market changes, achieve 28% higher inventory turnover, and retain 22% more customers than competitors. The analysis highlights how dynamic market-sensing capabilities restructure supply chains to translate consumer insights into operational advantages. Implications: The model provides executives with strategic guidance for building co-evolving marketing and supply chain systems and introduces tools such as the Demand Response Scorecard. For academics, theory advances by linking dynamic capabilities, market orientation, and operational flexibility, promoting a shift from market-responsiveness to market-propulsion.